The level of political participation among youth of Brgy. Sulangan, Guiuan, E. Samar. - Abayon, Joenard (Tacloban City Joenard Abayon [and] Riza Baldizar Odullo, 2010)
Barangay Sulangan is one of the barangay of Guiuan, Eastern Samar. Since the manner in which citizens participate in their political process is integral to the manner in which the system functions, the question of how and why persons become involved in politics is germane to the concerns of every man. Hence, it is for this reasons that the researchers become interested in studying the level of political participation among the youth. This study aims to determine the level of political participation the youth have and how it is affected by their socio-economic and demographic factors.
The study was conducted in Barangay Sulangan, Guiuan, Eastern Samar. The respondents of this study were determined through simple random sampling with fishbowl method. There were 127 respondents in this study.
The study employed a descriptive-correlational study method. Relevant data collected were statistically processed and analyzed with the used of descriptive statistics such as mean, standard deviation, p-value, eta, r-value, and the point biserial to establish relationships.
Results have shown that majority of the respondents are 16 years old. Most of them are females and are students in high school. Most of the youth are single and not have a family of their own yet. Overall, the youth of Barangay Sulangan has a high level of political participation. This implied that the youth are very much active when it comes to political issues. Moreover, there is no significant relationship between the socio-economic and demographic variables of the respondents and their level of political participation.
Results of this study are important because this will give an insight to on youth's political behavior and the extent of their political participation in the Philippine government. This may also give insights on how to engage people to participate and get involved in political activities.
Undergraduate thesis (B.A.S.S. Political Science)--University of the Philippines, Tacloban
Keywords: Social Science